Layanan Konseling Kelompok untuk Meningkatkan Rasa Percaya Diri - Eko Yudianto; Arifin Nur Budiono; Fakhruddin Mutakin (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2021)
Low self esteem can prevent a person from achieving the desired personal success in his future life. Based on the initial study by observing the data obtained about 57 %of students who experince self confidence. This study aims to increase the intensity of self confidence through group counseling. Yhe type of research used is guidance and counseling action research. The procedure used is a cycle model. Based on the results of the study, the first cycle of the first meeting of the respondents were still students showing ow self esteem. It is shown from the activeness, interst of students, enthusiasm of student, and conducive to students only around 60-66%. The second meeting, respondents have shown a better condition, which is around 74%. Cycle two the first meeting, around 80%. The second meeting, student avtivity. Student interest, student enthusiasm and student conduciveness increased, ranging from 89-96%. Group counseling services are one of the recommended aids to help students who exspirince low self esteem. Keywords: Group Conseling; Self Confodence